170: SHORT AND LONG TERM OUTCOMES IN ELDERLY PATIENTS WITH ESOPHAGEAL CANCER: UPFRONT ESOPHAGECTOMY COMPARED TO SURGERY AFTER NEOADJUVANT TREATMENTS. (23rd April 2022) - Moletta, L; Capovilla, G; Pierobon, E S; Carrillo, L; Ciccioli, E; Zanchettin, G; Provenzano, L; Salvador, R; Costantini, M; Merigliano, S; Valmasoni, M
Abstract: Background and aim: The current standard of care in treating locally-advanced esophageal cancer has been established after the publication of the landmark CROSS trial and several others, which demonstrated an overall survival benefit from preoperative chemoradiation prior to esophagectomy in this setting. However, elderly patients have been generally excluded from randomized study protocols, so literature regarding the choice of the best treatment approach for resectable esophageal cancer in patients older than 75 years old is limited. The aim of this study was to characterize outcomes associated with neoadjuvant chemoradiation prior to esophagectomy, compared to esophagectomy alone, in older patients with esophageal cancer. Methods: We conducted a retrospective study in patients ≥75 years with locally-advanced esophageal cancer (both adenocarcinoma -EAC and squamous cell carcinoma -SCC) undergoing esophagectomy ± neoadjuvant chemoradiation at our Center between 2000 and 2020. Results: A total of 141 patients were included in the study. Patients were subcategorized into two groups: patients undergoing upfront surgery (SURG, n = 97) and patients undergoing neoadjuvant therapy before surgery (NAT, n = 44). Patients in the NAT group experienced a significantly higher postoperative morbidity when compared to the SURG group. Overall survival (21 months and 25 months, p = 0.8883) and cancer-related survival (20 and 25 months, p 0.8052) were not statistically different between the SURG and the NAT group. When looking to the histology, OS for EAC and for SCC did not significantly differ between the 2 groups. We subcategorized patients according to their final pathological stage into patients with pTNM stage I and II, and patients with stage III and IV. Among patients with EACs stage III-IV, the NAT group experienced a significant benefit in OS when compared to the SURG group. Univariate analysis for risk factors for postoperative morbidity showed a significant association between NAT and postoperative complications (p 0, 0336). Multivariate analysis confirmed neoadjuvant therapy as an independent prognostic factor for morbidity ( P 0, 0226). Conclusion: In our study, patients undergoing NAT before surgery experienced a higher postoperative morbidity when compared to patients undergoing upfront esophagectomy. Further studies are needed to identify which older patients are most suitable for neoadjuvant therapy before esophagectomy.